The Exploration of Network Coding in IEEE 802.15.4 Networks - Deze Zeng; Song Guo; Victor Leung; Jiankun Hu (International Journal of Digital Multimedia Broadcasting)
Wireless personal area networks (WPANs) are getting popular in a variety of fields such as smart home, office automation, and e-healthcare. In WPANs, most devices are considerably energy constrained, so the communication protocol should be energy efficient. The IEEE 802.15.4 is designed as a standard protocol for low power, low data rate, low complexity, and short range connections in WPANs. The standard supports allocating several numbers of collision-free guarantee time slots (GTSs) within a superframe for some time-critical transmissions. Recently, COPE was proposed as a promising network coding architecture to essentially improve the throughput of wireless networks. In this paper, we exploit the network coding technique at coordinators to improve energy efficiency of the WPAN. Some related practical issues, such as GTS allocation and multicast, are also discussed in order to exploit the network coding opportunities efficiently. Since the coding opportunities are mostly exploited, our proposal achieves both higher energy efficiency and throughput performance than the original IEEE 802.15.4.